-9(v+3)+2v+7=5v+11

Simple and best practice solution for -9(v+3)+2v+7=5v+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9(v+3)+2v+7=5v+11 equation:


Simplifying
-9(v + 3) + 2v + 7 = 5v + 11

Reorder the terms:
-9(3 + v) + 2v + 7 = 5v + 11
(3 * -9 + v * -9) + 2v + 7 = 5v + 11
(-27 + -9v) + 2v + 7 = 5v + 11

Reorder the terms:
-27 + 7 + -9v + 2v = 5v + 11

Combine like terms: -27 + 7 = -20
-20 + -9v + 2v = 5v + 11

Combine like terms: -9v + 2v = -7v
-20 + -7v = 5v + 11

Reorder the terms:
-20 + -7v = 11 + 5v

Solving
-20 + -7v = 11 + 5v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-5v' to each side of the equation.
-20 + -7v + -5v = 11 + 5v + -5v

Combine like terms: -7v + -5v = -12v
-20 + -12v = 11 + 5v + -5v

Combine like terms: 5v + -5v = 0
-20 + -12v = 11 + 0
-20 + -12v = 11

Add '20' to each side of the equation.
-20 + 20 + -12v = 11 + 20

Combine like terms: -20 + 20 = 0
0 + -12v = 11 + 20
-12v = 11 + 20

Combine like terms: 11 + 20 = 31
-12v = 31

Divide each side by '-12'.
v = -2.583333333

Simplifying
v = -2.583333333

See similar equations:

| Sin^2(x)+9sin(x)+8=0 | | (2x+3)(3x^2-2x+1)= | | 6n=0.84 | | 15x-13=12x+41 | | 105-3t-32+8t-20=-72+6t-4 | | 2x+3x+3= | | -5=-3[x+11]-17 | | 7(5x-18)=259 | | 3(2x-9)=4(x+1) | | y=20+.9x | | 3(4.32x)+3.41y=65.48 | | 5/13=9/x | | 10(6x+2)=560 | | 3(4.32x)+3.41x=65.48 | | 1/13y=65 | | x=20+.9y | | y(y-4)=0 | | 6(x-9)=234 | | 90+51=180 | | c+51=10 | | 3x^4-192x= | | x/10-6=-3 | | 90+51+x=180 | | 4*(x+2)=-14 | | 6(5x+14)=384 | | √21/9 | | 20x^6+54x^5+10x^4= | | 9x+8=10x-13 | | Px+8=10x-13 | | ((-2)/(-5x-2))0 | | =ln(4x^2) | | 132=x+(3x-24) |

Equations solver categories